2003
DOI: 10.1590/s0103-84782003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Custo energético de construção de uma instalação para armazenagem de feno

Abstract: O trabalho teve como objetivo obter uma estimativa da energia empregada na construção de uma estrutura utilizada para armazenamento de fardos de feno, em um sistema de produção animal. Para tanto utilizaram-se os coeficientes energéticos levantados pela Fundação Centro Tecnológico de Minas Gerais (CETEC). O valor obtido foi de 587,09 MJ.m-2, o qual foi amplamente diferente daqueles observados na literatura. Da energia total empregada na construção da instalação os itens fechamentos, estrutura de cobertura, pis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
2
7
0
12
Order By: Relevance
“…These results are corroborated by ANGONESE et al (2006), & SANTOS & LUCAS JUNIOR (2004) and SOUZA et al (2009) that also showed higher consumption in the category of direct energy. In Table 6, it is shown the preponderance of direct energy through ration (80.57%) used as animals´ food.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…These results are corroborated by ANGONESE et al (2006), & SANTOS & LUCAS JUNIOR (2004) and SOUZA et al (2009) that also showed higher consumption in the category of direct energy. In Table 6, it is shown the preponderance of direct energy through ration (80.57%) used as animals´ food.…”
Section: Resultssupporting
confidence: 74%
“…For this same parameter, ANGONESE et al (2006) have evaluated the energy efficiency of such system in the finishing phase and have found out that the ration represented 95.28% of the total direct energy. In that same line of thought, SANTOS & LUCAS JUNIOR (2004) worked with the energy balance in broiler sheds and also showed that the diet was the largest component of energy intake, representing 86.50% of all the energy consumed directly by farming system.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations